Program complex «intellectual clinic»: clinic management system - Злепко, Сергій Макарович; Костішин, Сергій Володимирович; Овчарук, Тетяна Ігорівна; Сєргєєва, Вероніка Володимирівна (Eastern-European Journal of Enterprise Technologies, 2010)
In this paper the automated clinical management system was considered. The demands to the hardware were made and the structure of software part of the frame was suggested, which is based on the functional purpose of local modules.